Family rhythms : The changing textures of family life in Ireland - Gray, Jane; Ralph, David; Geraghty, Ruth (Book collections on Project MUSE., 2017)
This textbook draws on original in-depth interviews with people of different ages to introduce contemporary scholarship on the family and to illustrate how Irish families have adapted and changed over time.